Psychological health and its relationship with academic adaptation among the students of the faculty of sports sciences at Mu'tah University in the light of corona pandemic - محمود شنطاوي, معتصم; سعيد السعيدين, محمد (sports creativity, 2025)
This study aimed at identifying psychological health and its relationship with academic adaptation among the students of the faculty of sports sciences at Mu'tah University in the light of corona pandemic as well as identifying whether there are statistically significant in psychological health and its relationship with academic adaptation among the students of the faculty of sports sciences at Mu'tah University in the light of corona pandemic according to the variables of ( gender, academic year, educational qualification). The researchers used the descriptive approach due to its compatibility to the study nature and objectives. The study sample consisted of (99) male and female students from the faculty of sports sciences at Mu'tah University who were chosen by the simple random way. The questionnaire was used as the study instrument for data collection and (SPSS) was used for data analysis. The results showed that the level of academic adaptation among the students of the faculty of sports sciences at Mu'tah University in the light of corona pandemic was high. The study revealed that the level of psychological health among the students of the faculty of sports sciences at Mu'tah University in the light of corona pandemic was medium. The results revealed that there are no statistically significant differences attributed to the variables of (gender, academic year, educational qualification) and that there is a positive relationship between psychological health and academic adaptation. The researchers recommended the necessity of havingmore communication with the faculty members inside the faculty of sports sciences as well as holding electronic seminars via (Zoom) application concerning psychological health and adaptation with corona pandemic.